Aspects of knowledge : preserving and reinventing traditions of learning in the Middle Ages - Cesario, Marilina; Magennis, Hugh (Manchester medieval literature and culture., 2018)
This book investigates the role of 'texts' - including books, maps, stones and caskets - in the conveyance and transformation of knowledge and ideas throughout the Middle Ages. It contains original contributions by leading medievalists, who explore the topic from different yet complementary angles, offering diverse interdisciplinary and multi-cultural approaches on a wide variety of subjects.